Post modification of MOF derived carbon via g-C3N4 entrapment for an efficient metal-free oxygen reduction reaction - Pandiaraj, Sekar; Aiyappa, Harshitha Barike; Banerjee, Rahul; Kurungot, Sreekumar (Chemical Communications, 2014)
High surface area carbon with a nitrogen content of 7.0% is derived from MOF via in situ g-C3N4 formation. The material shows excellent ORR activity with an onset potential of 0.035 V (vs. Hg/HgO) in alkaline medium apart from high durability and strong disinclination towards methanol crossover.